GE_GERICHTE P/4600/2015 vom 22. April 2016 - GE Cour de justice (2016)
DISPOSITIONS PÉNALES DE LA LETR; DIRECTIVE 2008/115/CE; ACQUITTEMENT ; INDEMNITÉ(EN GÉNÉRAL) | LEtr.115.1b; CPP.135; CPP.428; CPP.429